Synthesis and properties of phospha[5]helicenes bearing an inner-rim phosphorus center - Md. Shafiqur Rahman (2020)
New phospha[5]helicene derivatives featuring angular fusion of phosphole and carbohelicene moieties have been synthesized using 7-hydroxybenzo[b]phosphole oxide as a key intermediate, which can be regioselectively prepared through one-pot multicomponent coupling. The structural behavior of the present phospha[5]helicene oxide, sulfide, and gold complex in the solid and solution states, along with DFT calculations, demonstrated close correlation between the P-centered chirality and the helical chirality as well as facile helicity inversion and equilibrium between the diastereomers in solution.